Market Orientation Determinants: Reflections from Academics in Universities of Technology in South Africa - Mokoena, B A; Dhurup, M (Journal of Economics and Behavioral Studies, 2016)
Internationally, universities have come under increased pressure to respond to the changing market environment. A new axis for higher education institutions (HEIs) is a key to successful marketing, which lies in identifying the core business of institutions. Market orientation more closely reflects a philosophy that will not only serve to bring unity of purposes in HEIs, but serves as an indispensable tool that can assist HEIs to deliver their core business. The dynamics in the HE environment, the growth potential and the regulatory challenges make universities of technology (UoTs) ideal institutions for a study on the implementation of market orientation. It is against this backdrop that this paper considers the factors contributing to market orientation through the lenses of South African UoT academics through a quantitative study; 507 (n=507) academics participated in the study. Data are analysed through exploratory (to determine the factor structure) and confirmatory factor analysis (to confirm factor structure), descriptive and correlation analysis (to analyse the composition of the sample and to establish validity). Through the factor analysis procedure, seven factors were established, namely intelligence generation, inter-functional coordination, student-orientation, market intelligence dissemination, intelligence response design, intelligence response implementation and interdepartmental dynamics as a basis for operationalising the marketing orientation concept among UoTs. Through confirmatory factor analysis, the identified components seem to encapsulate the determinants of UoTs appropriately. From a practical standpoint, top management of universities could use these core market orientation factors to guide their strategic marketing plans and their strategic imperatives with the universities vision and mission in order to remain relevant and competitive. Future studies could expand these factors to provide a better understanding within HEIs in relation to their various stakeholders.